2021
DOI: 10.1002/bab.2251
|View full text |Cite
|
Sign up to set email alerts
|

Application crude multienzyme extract from Aspergillus niger as a pretreatment for the extraction of essential oil from Croton argyrophyllus leaves

Abstract: Leaves of Croton argyrophyllus contain essential oil with promising active components for the development of drugs and botanical insecticides. In this study, we evaluated the enzymatic pretreatment process to increase the extraction of essential oil from fresh and dried leaves of C. argyrophyllus. Pretreatment was carried out using a crude multienzymatic extract obtained via solid‐state fermentation of forage palm by Aspergillus niger, and the extraction was performed by hydrodistillation. A Doehlert matrix wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 76 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…], since the plant cell wall is composed of a rigid complex of carbohydrates (cellulose, hemicellulose, xylan, pectin and lignin) which are arranged and connected in a well-organized manner, forming a material with a rigid and highly resistant structure. Therefore, it can requires the joint action of enzymes with different functions in order to be broken down [ 2 , 10 ]. Those enzymes could be: cellulases for hydrolyzing cellulose and generating monomer units making it possible both to localize and to destructure the substrate and thus facilitating the enzyme-substrate interaction; hemicellulases and accessory enzymes (unplugging glycoside hydrolases and carbohydrate esterases) for facilitating the attachment of enzymes to insoluble polysaccharides in particular that of the starch present in the plant cell wall which will promote the release of essential oils in the storage glands by hydrolysis ; possible enzymes degrading or modifying lignin which is responsible for rigidity and impermeability since it is a large group of complex aromatics polymers, representing between 10 and 30% of the dry matter of plant cell walls [ 10 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…], since the plant cell wall is composed of a rigid complex of carbohydrates (cellulose, hemicellulose, xylan, pectin and lignin) which are arranged and connected in a well-organized manner, forming a material with a rigid and highly resistant structure. Therefore, it can requires the joint action of enzymes with different functions in order to be broken down [ 2 , 10 ]. Those enzymes could be: cellulases for hydrolyzing cellulose and generating monomer units making it possible both to localize and to destructure the substrate and thus facilitating the enzyme-substrate interaction; hemicellulases and accessory enzymes (unplugging glycoside hydrolases and carbohydrate esterases) for facilitating the attachment of enzymes to insoluble polysaccharides in particular that of the starch present in the plant cell wall which will promote the release of essential oils in the storage glands by hydrolysis ; possible enzymes degrading or modifying lignin which is responsible for rigidity and impermeability since it is a large group of complex aromatics polymers, representing between 10 and 30% of the dry matter of plant cell walls [ 10 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was noticed that the highest yield (1.94%) could be attained on 10 days of fermentation with 4 h of distillation. This finding suggested that it might be take a certain time for the endophytes to grow and enable the synthesis of specific enzymes to break the glycosidic bonds that unite the polysaccharides to the plant cell wall and thus, causing ruptures in the oil storage glands which will facilitate extraction [ 2 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations